Feasibility and Prognostic Value of Stress Echocardiography in Obese, Morbidly Obese, and Super Obese Patients Referred for Bariatric Surgery. Issue 7 (17th December 2013) - Supariwala, Azhar; Makani, Harikrishna; Kahan, Jonathan; Pierce, Matthew; Bajwa, Farhan; Dukkipati, Sai Sreenija; Teixeira, Julio; Chaudhry, Farooq A.
<x xml:space="preserve">Abstract</x> Background Stress echocardiography (SE) is clinically used in the risk stratification and prognosis of patients with coronary artery disease. Due to multiple comorbidities, obese patients have increased risk of adverse cardiovascular events perioperatively in noncardiac surgery. The aim of this study was to investigate the feasibility of SE in morbidly obese patients undergoing bariatric surgery. Methods Consecutive patients referred for SE for preoperative evaluation prior to bariatric surgery from January 2002 to July 2011 formed the study cohort. Contrast was used to define the endocardial border in patients with poor acoustic windows. All‐cause mortality data were obtained from Social Security Death Index. Results Six hundred fifty‐two patients (47 ± 10 years, 84% females) with the mean follow‐up of 3.0 ± 2.7 years and mean body mass index (BMI) of 47 ± 9 kg/m² were included in this analysis. Dobutamine SE was performed in 65% of patients compared to exercise SE in 35%. Patients with higher BMI were more likely to undergo dobutamine SE (P < 0.0001). Similarly, incidence of poor acoustic windows and contrast use was higher in those with increased BMI (P < 0.001). Contrast use was higher in patients undergoing dobutamine SE (39%) versus exercise (25%), (P = 0.002). 19 patients (3%) had an abnormal SE and 8 patients (1.2%) died during the follow‐up period. Conclusion Stress echocardiography is feasible in the morbidly obese patients. Patients with higher BMI were more likely to undergo dobutamine SE and have higher incidence of poor acoustic windows and contrast use.